2022
DOI: 10.3389/fimmu.2022.795972
|View full text |Cite
|
Sign up to set email alerts
|

Neoadjuvant Immunotherapy for MSI-H/dMMR Locally Advanced Colorectal Cancer: New Strategies and Unveiled Opportunities

Abstract: Patients with locally advanced colorectal cancer (LACRC) have a high risk of recurrence and metastasis, although neoadjuvant therapy may provide some benefit. However, patients with high microsatellite instability/deficient mismatch repair (MSI-H/dMMR) LACRC receive little benefit from neoadjuvant chemoradiotherapy (nCRT) or neoadjuvant chemotherapy (nCT). The 2015 KEYNOTE-016 trial identified MSI-H/dMMR as a biomarker indicative of immunotherapy efficacy, and pointed to the potential use of immune checkpoint … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
47
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 74 publications
(50 citation statements)
references
References 48 publications
1
47
0
2
Order By: Relevance
“…In the past, immune factors in the nCRT response of LARCs have been largely ignored. Recently, the presence of pretherapy immune cell infiltration correlated with response to radiotherapy or chemotherapy in LARC has gradually begun to be emphasized (27)(28)(29). In consequence, identifying a reliable and feasible scoring system related to the immune microenvironment may play a significant role in the clinical management of LARCs.…”
Section: Discussionmentioning
confidence: 99%
“…In the past, immune factors in the nCRT response of LARCs have been largely ignored. Recently, the presence of pretherapy immune cell infiltration correlated with response to radiotherapy or chemotherapy in LARC has gradually begun to be emphasized (27)(28)(29). In consequence, identifying a reliable and feasible scoring system related to the immune microenvironment may play a significant role in the clinical management of LARCs.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, some studies have reported that patients with MSI-H rectal cancers showed worse survival [ 21 22 ], which is in accordance with the poor response to nCRT in the present study. These results may be the basis for performing tailored treatments such as neoadjuvant immunotherapy in patients with MSI-H rectal cancer [ 23 ] according to the results of pretreatment MSI testing on colonoscopic biopsy [ 18 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…As a result, pembrolizumab was approved by the FDA for the treatment of MSI-H/dMMR cancer that are unresectable and have metastasized. [14] In the CheckMate-142 study, [15] nivolumab alone and nivolunmab plus ipilimumab were used to treat dMMR/MSI-H colorectal cancer; the patients were followed up for a median of 21 and 25.4 months, respectively, and demonstrated objective response rates of 34% and 58%, respectively. Furthermore, the nivolunmab plus ipilimumab group had a disease control rate of 81%, 12-month progression-free survival(PFS) rate of 71%, and 12-month overall survival rate of 85%.…”
Section: Discussionmentioning
confidence: 99%